Stem cell-derived exosomal transcriptomes for wound healing - Chen, Guiling; Chen, Hankun; Zeng, Xiang; Zhu, Wei (Frontiers in Surgery, 2022)
Wound healing is a complex and integrated process of the interaction of various components within the injured tissue. Accumulating evidence suggested that stem cell-derived exosomal transcriptomes could serve as key regulatory molecules in wound healing in stem cell therapy. Stem cell-derived exosomal transcriptomes mainly consist of long noncoding RNAs (lncRNAs), microRNAs (miRNAs), circular RNAs (circRNAs) and messenger RNAs (mRNAs). In this article we presented a brief introduction on the wound repair process and exosomal transcriptomes. Meanwhile, we summarized our current knowledge of the involvement of exosomal transcriptomes in physiological and pathological wound repair process including inflammation, angiogenesis, and scar formation.